2010
DOI: 10.1159/000313559
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Black-Currant Extract on Negative Lens-Induced Ocular Growth in Chicks

Abstract: Aim: To evaluate the effects of orally administered black-currant (BC) extract on the enlargement of globe component dimensions induced in chicks by wearing negative lenses. Methods: Negative lenses (–8 D) were worn on the right eyes by 8-day-old chicks, and their fellow eyes acted as controls. BC extract and distilled water (vehicle control) were orally administered once a day for 3 days. To confirm the effect of BC anthocyanins (BCAs), they were intravenously administered once a day for 3 days. Dimensions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 78 publications
0
17
0
Order By: Relevance
“…in chick myopia models, 29 and the ET-dependent vasodilation in the bovine ciliary body. 35 In the present study, to elucidate possible mechanisms of BCACs demonstrating beneficial effects toward GON progression, we assayed several serum biomarkers obtained from BCAC-treated and placebo-treated patients with OAG who had participated in our previous randomized, double-masked 24-month trial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…in chick myopia models, 29 and the ET-dependent vasodilation in the bovine ciliary body. 35 In the present study, to elucidate possible mechanisms of BCACs demonstrating beneficial effects toward GON progression, we assayed several serum biomarkers obtained from BCAC-treated and placebo-treated patients with OAG who had participated in our previous randomized, double-masked 24-month trial.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 The ACs in black currants (BC) in particular have been implicated in improvement of visual functions. [27][28][29] In our initial clinical trial, we found that systemic administration of BCACs (50 mg/day) to patients with OAG (n = 30) for 6 months caused a significant increase in the blood flows at the ONH (P < 0.05). 30 Furthermore, in the subsequent randomized, placebo-controlled, double-masked, 24-month trial, we demonstrated that patients with OAG administered with BCACs showed significantly less deterioration of mean deviation (MD) and increased ocular blood flows in comparison with placebo-treated patients during the 24-month trial period.…”
Section: Introductionmentioning
confidence: 99%
“…Upon oral administration, these 4 components were directly absorbed and presented as intact forms in plasma and then transferred beyond the blood-aqueous barrier and blood-retina barrier into ocular tissues including the retina, choroid and ciliary body [35]. In vitro evidence demonstrated that such BCACs transferred into ocular tissues caused several kinds of biological activities including stimulation of rhodopsin regeneration in frog retinas [36], suppression of ocular globe elongation in chick myopia models [37] in addition to the ET-dependent vasodilation in the bovine ciliary body [16]. In vivo experiments demonstrated that oral administration of the BCACs significantly improved dark adaptation and video display terminal work-induced transient refractive alteration in healthy human volunteers [15].…”
Section: Discussionmentioning
confidence: 99%
“…Myopia inhibition is possibly achieved by stimulation of endothelin-1B receptor, induction of nitric oxide production, relaxation of ciliary smooth muscle, and subsequent thinning out of the eye's lens. In a recent study using a chick model of myopia, BA was reported to show inhibitory effects on myopia [74]. Intriguingly, in terms of distribution in rats, BA concentrations in the eye tissue of sclera and choroid membrane were about 100-fold higher than blood concentration.…”
Section: Inhibitory Effects On Myopia and Mitigative Effects On Eye Fmentioning
confidence: 95%